Dietary trans and saturated fatty acids effects on semen quality, hormonal levels and expression of genes related to steroid metabolism in mouse adipose tissue. (15th March 2019) - Molaie, Solmaz; Shahverdi, Abdolhossein; Sharafi, Mohsen; Shahhoseini, Maryam; Rashki Ghaleno, Leila; Esmaeili, Vahid; Abed‐Heydari, Elham; Numan Bucak, Mustafa; Alizadeh, AliReza
Abstract: Our objectives were to assess sperm alteration and adipose tissue (AT) genes expression related to steroid metabolism subsequent to fatty acids consumption. Twenty‐nine mature male mice were divided into: fat diet (FD; n  = 15) and the control group ( n  = 14). FD group was fed with low level of trans and saturated fatty acids source for 60 days. Sperm parameters, levels of hormones and the mRNA abundance of the target genes in AT were assessed. The sperm concentration, total and progressive motilities were lower in FD group compared to that of control ( p  < 0.01). Blood estradiol levels increased in FD ( p  < 0.001), whereas no significant difference was observed in testosterone. The mRNA levels of StAR, CYP11A1, CYP17A1, 17βHSD7 and 17βHSD12 in AT of FD were higher than those of the control ( p  < 0.05). In contrast, mRNA level of Cyp19a1 in FD was significantly ( p  < 0.05) lower than that of control. 17βHSD12 and 17βHSD7 (as oestrogenic genes) increased, while 17βHSD5 and 17βHSD3 (as androgenic genes) remained unchanged, indicating that dietary trans/saturated fatty acids affect AT genes expression. Probably, sperm parameters were altered by increment of expression level of genes involved in oestrogenic metabolism rather than those engaged in androgenic metabolism after fatty acids consumption.